Current Approaches to Country Risk Analysis - Potyomkina, N.O.; Voshchyna, E.S.; Breiman, M.M. (Економічний вісник Донбасу, 2013)
This article deals with the topic of country risk analysis. Different approaches to this problem, ratings developed by international rating agencies and their grades were examined. Ukrainian performance in these ratings was examined, as well as reasons of such performance.